Bio equivalence Study of Two Different Film-coated Tablet Formulations of Losartan-Hydrochlorothiazide in Healthy Volunteers - Neves, Rita; Almeida, Susana; Filipe, Augusto; Spínola, Ana Cristina Franco; Abolfathi, Zohreh; Yritia, Mercedes; Ortuño, Jordi (Arzneimittelforschung, 2008)
The study was conducted in order to assess the bioequivalence of two film-coated formulations containing 100 mg of losartan (CAS 124750-99-8) and 12.5 mg of hydrochlorothiazide (CAS 58-93-5). Seventy-three healthy subjects were enrolled in arandomised, single-dose, open-label, two-way crossover study, with a minimum washout period of 7 days. A total of 21 blood samples were collected up to 36 h post-dosing.Losartan, losartan carboxy acid and hydrochlorothiazide levels were determined by liquid chromatography with tandem mass detection (lower limit of quantification: 1.01 ng/mL for hydrochlorothiazide, 2.02 ng/mL for losartan and 2.51 ng/mL for losartan carboxy acid). Pharmacokinetic parameters used for bioequivalence assessment (AUC0–t and Cmax as primary and AUC0–inf as secondary pharmacokinetic parameters) were determined from the losartan and hydrochlorothiazide concentration data using non-compartmental analysis. Data from losartan carboxy acid was reported and presented as supportive data. The 90% confidence intervals (obtained by ANOVA) for losartan were 97.05–118.48% for Cmax, 100.76–106.10% for AUC0–t and 100.80–106.10% for AUC0–inf whereas for hydrochlorothiazide the 90% confidence intervals obtained were 103.94–115.33% for Cmax 101.97–109.61% for AUC0–t and 101.77–109.02% for AUC0–inf, and for losartan carboxy acid the intervals obtained were 98.31–107.82% for Cmax, 97.89–104.30% for AUC0–t and 98.06–104.30% for AUC0–inf. All the 90% confidence intervals obtained for all the parameters assessed were within the predefined ranges (80–125%).Based on these results, it can be concluded that the evaluated formulations are bioequivalent in terms of rate and extent of absorption.
Keywords: Antihypertensive drugs; CAS 58-93-5; CAS 124750-99-8; Hydrochlorothiazide, bioequivalence; Losartan, bioequivalence